Efektivitas Latihan Relaksasi Otot Pernafasan terhadap Penurunan Nyeri Pada Pasien Pasca Cateterisasi Jantung - Uun Nurulhuda; Elya Netty (Jurnal Health Sains, 2021)
Cardiac catheterization is a mandatory procedure that is performed before heart surgery and has the highest level of accuracy (96% -99%) to detect abnormalities in the heart, especially coronary heart disease. Through relaxation exercises the nurse's respiratory muscles help patients achieve stable hemodynamics and prevent respiratory complications due to pain after cardiac catheterization. This study aims to identify the effectiveness of breathing muscle relaxation exercises on pain reduction in patients after cardiac catheterization. The design of this study was a quasi-experimental study with a pre-post test approach, which was conducted in May-July 2018. The research subjects used inclusion criteria, namely patients undergoing cardiac catheterization at the public hospital in the rebo market area. Measuring instruments in data collection use a structured format. Breathing muscle relaxation exercises are the variables in this study, while the dependent variable is the level of pain after cardiac catheterization. The results of the independent T test and paired T test and the general linear model repeated measures prove the existence of a significant difference in the level of pain between before and after the relaxation exercises of respiratory muscles (P = 0.000). The average level of pain in the intervention group before the deep breathing relaxation exercise was 3.9, while the average level of pain after the deep breathing relaxation exercise decreased to 2.7. While the average level of pain in the control group with a standard given from the hospital that is distraction is 2.6, while the average level of pain after exercise decreased to 1.6.